Carcinogen susceptibility is regulated by genome architecture and predicts cancer mutagenesis. (16th August 2017) - García‐Nieto, Pablo E; Schwartz, Erin K; King, Devin A; Paulsen, Jonas; Collas, Philippe; Herrera, Rafael E; Morrison, Ashby J
Abstract: The development of many sporadic cancers is directly initiated by carcinogen exposure. Carcinogens induce malignancies by creating DNA lesions (i.e., adducts) that can result in mutations if left unrepaired. Despite this knowledge, there has been remarkably little investigation into the regulation of susceptibility to acquire DNA lesions. In this study, we present the first quantitative human genome‐wide map of DNA lesions induced by ultraviolet (UV) radiation, the ubiquitous carcinogen in sunlight that causes skin cancer. Remarkably, the pattern of carcinogen susceptibility across the genome of primary cells significantly reflects mutation frequency in malignant melanoma. Surprisingly, DNase‐accessible euchromatin is protected from UV, while lamina‐associated heterochromatin at the nuclear periphery is vulnerable. Many cancer driver genes have an intrinsic increase in carcinogen susceptibility, including the BRAF oncogene that has the highest mutation frequency in melanoma. These findings provide a genome‐wide snapshot of DNA injuries at the earliest stage of carcinogenesis. Furthermore, they identify carcinogen susceptibility as an origin of genome instability that is regulated by nuclear architecture and mirrors mutagenesis in cancer. Synopsis: Genome‐wide mapping of UV‐induced DNA lesions in primary cells reveals strong correlations with melanoma mutation frequencies and with nuclear genome architecture, suggesting that peripheral repeat regions may absorb UV damage to protect euchromatin. Genome‐wide mapping of UV‐induced lesions provides a snapshot of DNA injuries prior to the onset of DNA repair. UV lesions accumulate in lamina‐associated heterochromatin at the nuclear periphery, while DNase‐accessible euchromatin is protected. Lamin‐enriched LINE repeats are most susceptible to damage. Many cancer driver genes are lamin‐associated at the nuclear periphery and show an intrinsic increase in carcinogen susceptibility. Abstract : Genome‐wide maps of UV‐induced DNA lesions in primary cells correlate with mutation frequency in melanoma, and show that heterochromatin at the nuclear periphery is particularly vulnerable to carcinogenic sunlight.